2014
DOI: 10.1128/jvi.01334-14
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Nef Function Is Associated with Early Control of HIV-1 Viremia

Abstract: Host and viral factors influence the HIV-1 infection course. Reduced Nef function has been observed in HIV-1 controllers during the chronic phase, but the kinetics and mechanisms of Nef attenuation in such individuals remain unclear. We examined plasma RNA-derived Nef clones from 10 recently infected individuals who subsequently suppressed viremia to less than 2,000 RNA copies/ml within 1 year postinfection (acute controllers) and 50 recently infected individuals who did not control viremia (acute progressors)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 83 publications
3
42
0
Order By: Relevance
“…Naturally occurring sequence variation in Nef can modulate its CD4 and HLA class I downregulation activities (33)(34)(35)(36)58). We therefore investigated the impact of B*13-associated polymorphisms on Nef function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Naturally occurring sequence variation in Nef can modulate its CD4 and HLA class I downregulation activities (33)(34)(35)(36)58). We therefore investigated the impact of B*13-associated polymorphisms on Nef function.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, this naturally occurring mutant combination, selected in vivo under B*13-mediated CTL pressure, conferred a functional cost to Nef's immune evasion activity. Although attenuation of Nef's HLA class I downregulation function as a consequence of CTL escape has been described previously (35,36), the mutations required to confer these effects are rare in vivo. The HLA-B*35-driven Nef-R75T and -Y85F escape mutations, when present together, reduced Nef's HLA class I downregulation activity nearly 2-fold, but this combination occurs in Ͻ0.2% of natural HIV-1 sequences (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other host responses, including the subject's more dominant T cell responses which exhibited consistent oligofunctionality, could have contributed to the virus control observed; particularly as this subject expressed the HLA B*81 allele which is overrepresented in viremic controllers [37]. Other viremic factors, variation in Nef-mediated immune evasion [38,39] or Gag-Protease replicative capacity [40] could have resulted in emergence of less fit and or less pathogenic viruses resulting in the lower setpoint. Given the number of variables in this, a single patient study, we cannot draw firm conclusions regarding the HIV-1 control observed.…”
Section: ------------------------------------------------------------mentioning
confidence: 97%